A Bis(dipyridophenazine)(2‐(2‐pyridyl)pyrimidine‐4‐carboxylic acid)ruthenium(II) Complex with Anticancer Action upon Photodeprotection1. (5th February 2014) - Joshi, Tanmaya; Pierroz, Vanessa; Mari, Cristina; Gemperle, Lea; Ferrari, Stefano; Gasser, Gilles
Abstract Improving the selectivity of anticancer drugs towards cancer cells is one of the main goals of drug optimization; the prodrug strategy has been one of the most promising. A light‐triggered prodrug strategy is presented as an efficient approach for controlling cytotoxicity of the substitutionally inert cytotoxic complex [Ru(dppz)2(CppH)](PF6)2 (C1; CppH=2‐(2‐pyridyl)pyrimidine‐4‐carboxylic acid; dppz=dipyrido[3, 2‐a:2′, 3′‐c]phenazine). Attachment of a photolabile 3‐(4, 5‐dimethoxy‐2‐nitrophenyl)‐2‐butyl (DMNPB) ester ("photocaging") makes the otherwise active complex C1 innocuous to both cancerous (HeLa and U2OS) and non‐cancerous (MRC‐5) cells. The cytotoxic action can be successfully unleashed in living cells upon light illumination (350 nm), reaching similar level of activity as the parent cytotoxic compound C1. This is the first substitutionally inert cytotoxic metal complex to be used as a light‐triggered prodrug candidate.